Effectiveness of whitening techniques in vital teeth today (Research, Society and Development, 2025)
Tooth whitening is a conservative, safe, and effective aesthetic procedure widely used to improve the appearance of the smile. Among the methods of execution, in-office techniques, supervised at-home techniques, and, in some cases, a combination of both stand out. Objective: To evaluate, through an literature review, the effectiveness of whitening techniques applied to specific teeth, focusing on a comparison between in-office and supervised at-home protocols. In addition, the mechanisms of action of whitening agents and the prevalence of tooth sensitivity as an adverse effect were developed. Methodology: The research was conducted in the Scielo, PubMed, and Google Scholar databases, using descriptors related to dental whitening and specific teeth. Articles in Portuguese and English, published between 2015 and 2025 with full texts and aligned with the objective of the review, were included. Results and Dissemination: A review of 20 studies on teeth whitening revealed that both in-office and at-home techniques are effective, differing only in the concentration of agents and tooth sensitivity. Hydrogen peroxide and carbamide peroxide act by releasing oxygen radicals that promote pigment oxidation. Sensitivity was the main adverse effect, which was reduced with the use of fluoride and proper professional supervision. Conclusion: Dental whitening, both in-office and with home supervision, proved to be effective and safe, with differences in speed and sensitivity. Success depends on the concentration of the agent, the exposure time, and proper professional supervision.